Free-edge effect on the tensile properties of 3D woven composites - Wu, Zengwen; Li, Ce; Liao, Feng; Liu, Gang; Zeng, Shan (Frontiers in Materials, 2023)
Free-edge effect is one of the factors affecting the mechanical properties of three-dimensional woven composites under tensile load. However, current research is relatively poorly understood regarding the effect of free-edge on the stiffness and strength of the material. This paper aims at examining the influence of free-edge effect on the mechanical properties of 3D woven composites under tension through experimental and simulation methods. The three-dimensional digital image correlation (DIC) technique is used to collect the full-field strains on the specimen surface during the test, and the stress-strain differences in different regions in the width direction are analyzed, and the overlap of the curves in each region is found to be high, indicating that the boundary effect has a small influence on the tensile properties of 3D woven composites. Experimental studies are conducted on specimens of different widths (within the range of 15-20 mm), and the results indicate that the differences in mechanical properties of 3D woven composites under tension loading in this width range are not significant. A progressive damage finite element model is developed for calculation and compared with experimental results, and it is found that the tensile properties of the material decreased when the width of the specimen is less than twice the size of the single cell. This study can provide certain data support for the study of the mechanical properties of 3D woven composites and enable the subsequent more in-depth study to provide a certain foundation.